2016
DOI: 10.1038/ncomms10634
|View full text |Cite
|
Sign up to set email alerts
|

Chronic stress in mice remodels lymph vasculature to promote tumour cell dissemination

Abstract: Chronic stress induces signalling from the sympathetic nervous system (SNS) and drives cancer progression, although the pathways of tumour cell dissemination are unclear. Here we show that chronic stress restructures lymphatic networks within and around tumours to provide pathways for tumour cell escape. We show that VEGFC derived from tumour cells is required for stress to induce lymphatic remodelling and that this depends on COX2 inflammatory signalling from macrophages. Pharmacological inhibition of SNS sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
266
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 256 publications
(280 citation statements)
references
References 68 publications
(104 reference statements)
11
266
0
3
Order By: Relevance
“…Recently published studies suggest that COX2/PGE 2 signaling is also important for the proliferation and renewal of bladder stem cancer cells (28). Macrophage-derived PGE 2 also promotes tumor cell dissemination, that is, spreading of metastatic malignant cell from parental tumor (29). Therefore, harnessing PGE 2 metabolism in the tumor-infiltrating myeloid cells, including tumor-associated macrophages and their predecessors MDSCs, could potentially exert the multipronged cancer therapeutic effects by (i) stimulating anti-tumor response through PD-L1 down-regulation and preserving function of immune T cells, (ii) attenuating renewal of cancer stem cells, and (iii) inhibiting metastatic cancer cell spreading.…”
Section: Resultsmentioning
confidence: 99%
“…Recently published studies suggest that COX2/PGE 2 signaling is also important for the proliferation and renewal of bladder stem cancer cells (28). Macrophage-derived PGE 2 also promotes tumor cell dissemination, that is, spreading of metastatic malignant cell from parental tumor (29). Therefore, harnessing PGE 2 metabolism in the tumor-infiltrating myeloid cells, including tumor-associated macrophages and their predecessors MDSCs, could potentially exert the multipronged cancer therapeutic effects by (i) stimulating anti-tumor response through PD-L1 down-regulation and preserving function of immune T cells, (ii) attenuating renewal of cancer stem cells, and (iii) inhibiting metastatic cancer cell spreading.…”
Section: Resultsmentioning
confidence: 99%
“…volumes (<30 μl) of blood could be repeatedly sampled from either the tail vein or saphenous vein in restrained unanesthetized mice (14); however, it is stressful for the animal and this may affect lymph flow (33,34). Short-term inhalation anesthesia could be used to limit this effect; however, at least in mice, the dynamics of lymph transport are relatively quick, which would require multiple anesthesia applications and blood samplings within a short period of time.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of β-adrenergic signaling is an emerging factor that promotes metastasis and accelerates cancer progression Sloan et al, 2010;Thaker et al, 2006). Cancer cells express β-adrenoceptors, whose activation results in increased invasion and metastasis in vivo (Creed et al, 2015;Le et al, 2016); this suggests that targeting the β-adrenergic signaling pathway might be a promising strategy to slow disease progression, especially for diseases such as triple-negative breast cancer and pancreatic cancer, which are often aggressive and have few treatment options once chemoresistance develops. Inhibition of β-adrenergic signaling is an especially promising therapeutic strategy: an effective antagonist for β-adrenergic receptors (βARs) are β-blocker drugs, which are already widely used to treat cardiac disease and hypertension (Barrese and Taglialatela, 2013;Wiysonge et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of β-adrenergic signaling is an especially promising therapeutic strategy: an effective antagonist for β-adrenergic receptors (βARs) are β-blocker drugs, which are already widely used to treat cardiac disease and hypertension (Barrese and Taglialatela, 2013;Wiysonge et al, 1996). β-blockers inhibit metastasis in vivo (Campbell et al, 2012;Creed et al, 2015;Le et al, 2016;Sloan et al, 2010;Sood et al, 2006) and analyses of cancer patient cohort data has revealed that coincidental use of β-blockers is linked to reduced metastasis and improved survival (Barron et al, 2011;Le et al, 2016;Melhem-Bertrandt et al, 2011;Powe et al, 2010). Recent mechanistic studies show that β-adrenergic signaling modulates metastasis by driving changes in the tumor microenvironment including vascular remodeling and immune cell recruitment Thaker et al, 2006).…”
Section: Introductionmentioning
confidence: 99%